Solvent Extraction Investigations on Pu(IV) and Th(IV) Complexes with Hydrophilic SO3-Ph-BTP and SO3-Ph-BTBP Ligands. Issue 3 (7th June 2019) - Steczek, Łukasz; Narbutt, Jerzy; Charbonnel, Marie-Christine; Moisy, Philippe
ABSTRACT: Complexation of Pu(IV) and Th(IV) cations by the title ligands – hydrophilic sulfophenyl triazinyl derivatives of bis-triazinyl-pyridine and -bipyridine – was studied in solvent extraction systems containing a TODGA extractant and one of these hydrophilic ligands. Stoichiometries and stability constants of the complexes formed in an acidic (HNO3 ) aqueous phase have been determined. The Pu(IV) complexes are significantly stronger than their Th(IV) analogues. Only two complexes of each metal with SO3 -Ph-BTP (1:1 and 1:2) have been detected, and only one (1:1) with SO3 -Ph-BTBP; both numbers being less than expected based on the coordination numbers of the metal ions and on the denticities of the ligands. Possible reasons of this discrepancy are discussed.